Biosynthesis of Copper Oxide Nanoparticles Using Streptomyces MHM38 and Its Biological Applications. (4th January 2021) - Bukhari, Sarah I.; Hamed, Moaz M.; Al-Agamy, Mohamed H.; Gazwi, Hanaa S. S.; Radwan, Hesham H.; Youssif, Asmaa M.
Abstract : Biosynthesis methods employing microorganisms have emerged as an eco-friendly, clean, and viable alternative to chemical and physical processes. The present study reports the synthesis of copper oxide nanoparticles (CuONPs) using cell-free culture supernatant of marine Streptomyces sp. MHM38. For the optimized production of CuONPs, the influence of some parameters, such as the concentration of copper sulfate (CuSO4 ), reaction time, filtrate to substrate ratio, and pH, was studied. 5 mM of CuSO4 was optimal for nanoparticle (NP) production. Well-defined CuONP formation occurred after 60 min of incubation when an equal volume of filtrate (cell-free supernatant) to substrate (CuSO4 solution) was added. UV-visible spectroscopy analysis of CuONPs exhibited a peak at 550 nm, which corresponds to the surface plasmon resonance of CuONPs. Most of the particles were spherical and were 1.72–13.49 nm when measured using a transmission electron microscope. The antimicrobial activity of CuONPs was determined using a well diffusion method against Enterococcus faecalis ATCC 29212, Salmonella typhimurium ATCC 14028, Pseudomonas aeruginosa ATCC 9027, Escherichia coli ATCC 8939, fungi ( Rhizoctonia solani, Fusarium solani, and Aspergillus niger ), and yeast ( Candida albicans ATCC 10237). The highest antimicrobial activities were recorded against Candida albicans ATCC 10237, whereas Salmonella typhimurium ATCC 14028 and Escherichia coli ATCC 8939 showed the less activity. The biochemical findings of the CuONP groups were significant (p < 0.05 ) with diminished levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), total and direct bilirubin, urea, and creatinine compared with the paracetamol group. Nonenzymatic and enzymatic antioxidants of the CuONP groups were significantly elevated (p < 0.05 ) in SOD and GSH levels, and exceptionally low nitric oxide (NO) and malondialdehyde (MAD) levels were found for the paracetamol group. The histopathological examination of the CuONP groups assured the impact of improving CuONPs against paracetamol-induced liver damage.